Targeting Tau to Treat Clinical Features of Huntington's Disease - Masnata, Maria; Salem, Shireen; de Rus Jacquet, Aurelie; Anwer, Mehwish; Cicchetti, Francesca (Frontiers in Neurology, 2020)
Huntington’s disease (HD) is an autosomal dominant neurodegenerative disorder characterized by severe motor, cognitive and psychiatric impairments. While motor deficits often confirm diagnosis, cognitive dysfunctions usually manifest earlier in disease progression and are consistently ranked among the leading factors that impact the patients’ quality of life. The genetic component of HD, a mutation in the huntingtin (HTT) gene, is traditionally presented as the main contributor to disease pathology. However, accumulating evidence suggests the implication of the microtubule-associated tau protein to the pathogenesis, and therefore proposes an alternative conceptual framework where tau and mutant huntingtin (mHTT) act conjointly to drive neurodegeneration and cognitive dysfunction. This perspective on disease etiology offers new avenues to design therapeutic interventions and could leverage decades of research on Alzheimer’s disease (AD) and other tauopathies to rapidly advance drug discovery. In this mini review, we examine the breadth of tau-targeting treatments currently tested in the preclinical and clinical settings for AD and other tauopathies, and discuss the potential application of these strategies to HD.